Stable water isotope data for the AH-1502 ice core drilled at the Allan Hills Blue ice area - Introne, Douglas; Kurbatov, Andrei V.; Mayewski, Paul A.; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2018)
Stable water isotope data for the ice core drilled at the Allan Hills Blue ice area have been generated under a collaborative effort by the University of Maine Climate Change Institute (NSF Award#1443306) and Princeton University (NSF Award# 1443263). This data set contains stable isotope data (dD, d18O) of meltwater samples collected from the ice core AH-1502 (76.73286 S, 159.35507 E) was drilled in 2015-16 field season to 197 meters below the surface.